European experience in the solution of cross-border environmental problems - Rainer Durth (Intereconomics, 1996)
In view of the ever greater demands placed on the environment worldwide and the limited resources available to meet this demand, cross-border environmental problems are expected to become an increasingly contentious issue in the next few decades. A case in point are international rivers and the problems that arise from the competing claims of the riparian states. In this regard a number of important lessons have been learnt in Europe.
Keywords: 330; Environment